2021
DOI: 10.4236/ajps.2021.124035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waterlogging Stress on the Physiological Characteristics and Secondary Metabolites of Herbaceous Peony (<i>Paeonia lactiflora</i> Pall.)

Abstract: Herbaceous peony is an ornamental plant with medicinal properties. Waterlogging can affect its yield and quality as it grows and matures. In this study, we subjected "Taohuafeixue", "Yangfeichuyu" and "Hongxiuqiu" herbaceous peony varieties to a simulated waterlogging stress treatment and investigated the effects of waterlogging on their physiological characteristics and the secondary metabolite contents in their leaves and roots. Short-term waterlogging caused the leaves to turn yellow or red and the roots to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…To survive waterlogging stress, they have evolved various strategies including the formation of aerenchyma and adventitious roots at the morphological level [ 7 ] and molecular responses, as determined by RNA-Seq in Arabidopsis [ 8 ], cotton [ 9 ], sesame [ 10 ], and other plants. Increasing research is focused on the roles of key pathways involved in adaption to waterlogging stress [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To survive waterlogging stress, they have evolved various strategies including the formation of aerenchyma and adventitious roots at the morphological level [ 7 ] and molecular responses, as determined by RNA-Seq in Arabidopsis [ 8 ], cotton [ 9 ], sesame [ 10 ], and other plants. Increasing research is focused on the roles of key pathways involved in adaption to waterlogging stress [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the period from November 2022 to April 2023, monthly precipitation in autumn at the Deliblato Sands was in line with the multi-year average, while precipitation in winter and early spring was above average, especially in April when precipitation was 86% higher than usual. According to Liu (2021), roots of herbaceous peonies become black and the foliage turns yellow or red due to temporary waterlogging. While waterlogging had no effect on plant height, leaf length or leaf area, it reduced the root-shoot ratio of tested herbaceous peony (Paeonia lactiflora Pall.)…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al ( 2019 ) indicated that the antioxidant enzyme activity (CAT, SOD, and POD) of Triarrhena sacchariflora Nakai was increased with WL treatments. Liu et al ( 2021 ) showed an increment in the activity of antioxidant enzymes (SOD, POD, and CAT) in all varieties of P. lactiflora under WL stress.…”
Section: Resultsmentioning
confidence: 99%
“…Ghodke et al ( 2018 ) reported that WL stress adversely affected the plant growth like the plant height, leaf length and leaf area in onion ( Allium cepa L.). Liu et al ( 2021 ) exhibited that plant height, leaf length, and leaf area were not affected by WL stress in three cultivars of Paeonia lactiflora Pall. Manurung et al ( 2019 ) evaluated the effect of drought stress on the growth parameters of Ficus deltoidea Jack using 4 different water field capacity (40%, 60%, 80% and 100%-C) levels.…”
Section: Resultsmentioning
confidence: 99%